Formulation, Characterization, and Antibacterial Study of Microsponge- Loaded Gel of Clarithromycin for Topical Drug Delivery - Tomar, Mohit K.; Pahwa, Shilpa; Tyagi, Lalit Kumar; Gupta, Chitra; Maan, Preeti; Sethi, Vandana Arora (Drug Delivery Letters, 2022)
Background: Microsponge drug delivery systems comprise spherical and porous microspheres for prolonged topical drug delivery. These systems considerably reduce the undesirable side effects, offering improved patient compliance and reduced dosing frequency. Objective: The present study focused on developing topical controlled release preparations of microsponges-loaded gel of clarithromycin to cure bacterial skin infections. Materials and Methods: Four batches of microsponges (F1, F2, F3, and F4) of clarithromycin (CLR) containing fixed amounts of clarithromycin (100 mg), dichloromethane (5 ml), polyvinyl alcohol (5 % w/v) and distilled water (25 ml) with varying polymer concentrations were prepared by the quasi-emulsion solvent diffusion method and evaluated for % Production Yield, % drug content, % encapsulation efficiency, particle size, polydispersity index (PDI) and % drug release characteristics. The selected microsponge formulation (F3) was incorporated in Carpopol 934 gel for topical application. The prepared gel (CLRMS-F3 Gel) was evaluated for physical characteristics, pH, spreadability, viscosity, and in vitro drug release. Furthermore, the gel formulation was compared with pure clarithromycin gel for antibacterial activity against the gram-positive (S. aureus) and gram-negative strain (E. coli.) using the cup and plate method. Results and Discussion: The F3 microsponge formulation exhibited a production yield of 83.75%, drug content (21.5 ± 0.50 %), and encapsulation efficiency of 86.04 ± 2.30%. Their particle size was satisfactory (3.80 ± 0.01 μm), and they were found to be spherical and porous in nature. F3 microsponges released 69.36 ± 1.27% of the drug over a period of 8 hrs and were incorporated into the gel formulations. The gel prepared using F3 microsponges was transparent, homogenous, and exhibited a pH of 6.8 ± 0.02, spreadability of 9.92 ± 0.44 g/cm, and viscosity of 35370.17 ± 493.09 centipoises. The CLRMS-F3 gel released 82.13 ± 0.47% drug in 12 hrs using a zero-order kinetic. The antibacterial activity studies revealed a higher potency against both S. aureus and E. coli of the prepared CLRMS-F3 gel compared to pure CLR gel and azithromycin standard. Conclusion: Based on the above study, it may be concluded that microsponges’ gel formulation can be potentially useful in improving topical drug delivery of antibacterial agents and can give better therapeutic efficacy.
Keywords: antibacterial activity